2016
DOI: 10.2151/jmsj.2016-001
|View full text |Cite
|
Sign up to set email alerts
|

Predictability Changes of Stratospheric Circulations in Northern Hemisphere Winter

Abstract: Practical predictability of the stratospheric circulation in the boreal winters during the period [2001][2002][2003][2004][2005][2006] has been examined using the archive of 1-month ensemble forecast datasets provided by the Japan Meteorological Agency. To investigate the predictability limit, two measures of the Root-Mean-Square Error (RMSE) and Anomaly Correlation (AC) have been used for the 10-hPa geopotential height field. In the winter stratosphere, an intermittent character of planetary wave activity cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…It is uncertain if the conclusion in this study based on this case can be generalized to other SSW events due to the peculiarities of the 2019 SSW event, which was initialized by wave‐1 but reinforced by wave‐3 and wave‐2 pulses leading to persistent splitting of the polar vortex. The relatively higher predictability of vortex displacement SSWs than vortex splitting events has been widely reported in previous studies (e.g., Ichimaru et al, ; Mukougawa & Hirooka, ; Rao et al, ; Taguchi, ) and similar predictability could be anticipated for this event during the peak‐1 period. The contribution of the rapid wave‐3 pulse to the SSW onset was also reported for the February 2005 warming event (Shi et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…It is uncertain if the conclusion in this study based on this case can be generalized to other SSW events due to the peculiarities of the 2019 SSW event, which was initialized by wave‐1 but reinforced by wave‐3 and wave‐2 pulses leading to persistent splitting of the polar vortex. The relatively higher predictability of vortex displacement SSWs than vortex splitting events has been widely reported in previous studies (e.g., Ichimaru et al, ; Mukougawa & Hirooka, ; Rao et al, ; Taguchi, ) and similar predictability could be anticipated for this event during the peak‐1 period. The contribution of the rapid wave‐3 pulse to the SSW onset was also reported for the February 2005 warming event (Shi et al, ).…”
Section: Discussionsupporting
confidence: 84%
“…Kalnay, 2003). Therefore, we could estimate that the predictable period in the troposphere (levels below 100 hPa) is~7 to 9 days; This is consistent with other work (e.g., Ichimaru et al, 2016). On the other hand, the predictable period in the stratosphere is generally longer than that of the troposphere.…”
Section: Impact On Forecasting Circulation Anomalies After Sswssupporting
confidence: 90%
“…Furthermore, Ichimaru et al . [] suggested by the analysis on several SSWs during 2001–2006 using the same ensemble forecast data set that the displacement type SSW tends to have a longer predictable period than the vortex splitting type SSW. On the other hand, by conducting deterministic hindcast experiments initialized at 1 day interval with a Hadley Center atmospheric general circulation model (HadGAM1) for four SSW events occurred in 1980s and 1990s, Marshall and Scaife [] indicated that there is no significant difference in the predictable period for the two types of the SSW.…”
Section: Introductionmentioning
confidence: 99%